Recent Advances in the Synthesis and Application of Benzocyclobutenones and Related Compounds - Flores-Gaspar, Areli; Martin, Ruben (Synthesis, 2013)
Benzocyclobutenones are an intriguing class of four-membered-ring ketones that have been used extensively as powerful synthetic intermediates in organic synthesis. Their high reactivity is primarily attributed to the unique high electrophilicity of the carbonyl unit and the ability to generate o-quinone dimethides, allowing a myriad of different transformations. However, the synthesis of benzocyclobutenones still represents a great challenge. This review provides an overview of the preparation, use and impact of benzocyclobutenones in organic synthesis. Selected applications in the synthesis of natural products are also described, in order to illustrate the utility of these compounds. 1 Introduction2 Synthetic Methods for Preparing Benzocyclobutenones2.1 [2+2]-Type Cycloadditions2.2 Metal-Mediated Intramolecular Cyclizations2.3 Metal-Catalyzed Cross-Coupling Reactions2.3.1 Carbon–Hydrogen Bond-Functionalization Events2.3.2 Stille Cross-Coupling Reactions2.4 Other Synthetic Methods for Preparing Benzocyclobutenones3 Synthetic Application of Benzocyclobutenones and Related Compounds3.1 Synthesis of Polycyclic Compounds via o-Quinone Dimethides3.1.1 Synthesis of α-Tetralones3.1.2 Synthesis of Benzo[n]annulenes3.1.3 Synthesis of Naphthalene Derivatives3.1.4 Synthesis of Anthraquinones3.1.5 Synthesis of Benzodiazepines3.1.6 Synthesis of Tetrahydronaphthalenes3.1.7 Synthesis of Isochromanones3.2 Synthesis of Fused Rings via Non-Electrocyclization Techniques3.2.1 Ring Expansions from Four- to Five-Membered Rings3.2.2 Ring Expansions from Four- to Six-Membered Rings3.3 Other Synthetic Applications3.3.1 Tricarbonylchromium Complexes3.3.2 Base-Induced Carbon–Carbon Bond Cleavage3.4 Benzocyclobutenones and Their Derivatives in Natural Product Synthesis4 Conclusions
Keywords: benzocyclobutenones; cycloaddition; C–C bond cleavage; o-quinone dimethides; fused π-aromatic systems; ring expansion